Monotherapy or Combination Therapy of Oleanolic Acid? From Therapeutic Significance and Drug Delivery to Clinical Studies: A Comprehensive Review - Shaharyar, Md. Adil; Banerjee, Tanmoy; Sengupta, Monalisha; Bhowmik, Rudranil; Sarkar, Arnab; Mandal, Pallab; Alzarea, Sami I.; Ghosh, Nilanjan; Akhtar, Jamal; Kazmi, Imran; Karmakar, Sanmoy (Planta Medica, 2025)
Oleanolic acid is a pentacyclic triterpenoid molecule widely distributed throughout medicinal plants. This naturally occurring oleanolic acid has attracted considerable interest due to its wide range of pharmacological characteristics, notably its cytotoxic effects on various human cancer cell lines, making it a potential candidate for extensive therapeutic uses. In vivo studies have shown that oleanolic acid possesses hepatoprotective, cardioprotective, anti-inflammatory, and antimicrobial properties. The inherent obstacles of oleanolic acid, such as low permeability, limited bioavailability, and poor water solubility, have restricted its therapeutic applicability. However, recent developments in drug delivery techniques have given oleanolic acid an additional advantage by overcoming issues with its solubility, stability, and bioavailability. This review briefly summarises the signalling pathways involved in the pharmacological activities of oleanolic acid as a monotherapy and in combination with other drugs. The review devotes a substantial portion to explaining the formulation developments, emphasising nanotechnology as a key factor in the improvement of the therapeutic potential of oleanolic acid. Several investigated novel formulations have been discussed, including liposomes, nanoemulsions, phospholipids, and polymeric nanoparticles, emerging synergistically as an efficient delivery of oleanolic acid and several other drugs. Based on our literature evaluation, it can be inferred that combination therapy had a more favourable outcome than using oleanolic acid alone in in vivo trials, primarily due to its synergistic effects. However, it is essential to note that this finding was inconsistent across all investigations. The combination of oleanolic acid with other drugs has not yet been considered for clinical trials. However, it is interesting that neither therapy has obtained approval from the U. S. Food and Drug Administration.
Keywords: oleanolic acid; combination therapy; pharmacological activity; drug delivery